Structural and Enzymological Evidence for an Altered Substrate Specificity in Okur-Chung Neurodevelopmental Syndrome Mutant CK2αLys198Arg - Werner, Christian; Gast, Alexander; Lindenblatt, Dirk; Nickelsen, Anna; Niefind, Karsten; Jose, Joachim; Hochscherf, Jennifer (Frontiers in Molecular Biosciences, 2022)
Specific de novo mutations in the CSNK2A1 gene, which encodes CK2α, the catalytic subunit of protein kinase CK2, are considered as causative for the Okur-Chung neurodevelopmental syndrome (OCNDS). OCNDS is a rare congenital disease with a high phenotypic diversity ranging from neurodevelopmental disabilities to multi systemic problems and characteristic facial features. A frequent OCNDS mutation is the exchange of Lys198 to Arg at the center of CK2α’s P+1 loop, a key element of substrate recognition. According to preliminary data recently made available, this mutation causes a significant shift of the substrate specificity of the enzyme. We expressed the CK2αLys198Arg recombinantly and characterized it biophysically and structurally. Using isothermal titration calorimetry (ITC), fluorescence quenching and differential scanning fluorimetry (thermofluor), we found that the mutation does not affect the interaction with CK2β, the non-catalytic CK2 subunit, and that the thermal stability of the protein is even slightly increased. However, a CK2αLys198Arg crystal structure and its comparison with wildtype structures revealed a significant shift of the anion binding site harboured by the P+1 loop. This observation supports the notion that the Lys198Arg mutation causes an alteration of substrate specificity which we underpinned here with enzymological data.